Gandhi jivan : vividha ayam - Soni, Vedprakaś (Dilli : Janavani Prakaśan, 2010)
Short biographical details of Mahatma Gandhi, 1869-1948, Indian statesman
Keywords: Mahatma Gandhi - biografija -- Mahatma Gandhi - 1869-1948; indijski državnici - biografije